Kontrola działalności badawczo-rozwojowej - Majerczyk, Halina (The research and development sphere's control conveys in many dimensions. One of them are costs. First, the costs are planed, then they are compared with actual costs to get deviations. The deviations are analysed. The other deviations of the research and development sphere's control are time and progress of work, 2005)
The research and development sphere's control conveys in many dimensions. One of them are costs. First, the costs are planed, then they are compared with actual costs to get deviations. The deviations are analysed. The other deviations of the research and development sphere's control are time and progress of work.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 225-230